Forthcoming risk of invasive species Arundo donax: global invasion driven by climate change - Poudel, Anil; Lee, Yong Ho; Adhikari, Prabhat; Adhikari, Pradeep; Hong, Sun Hee (Frontiers in Ecology and Evolution, 2025)
Arundo donax ranks among the world’s 100 most invasive weed species, posing significant threats to native biodiversity, agriculture, and natural ecosystems. Global climate change, characterized by increasing temperatures and increased human activities, is projected to amplify the risk of A. donax invasion worldwide. In this study, species distribution modeling via the maximum entropy algorithm was employed to predict the potential distributions of species under current and future climate scenarios on the basis of the following shared socioeconomic pathways (SSPs): SSP2-4.5 and SSP5-8.5. Our study revealed that the human influence index (HII), annual mean temperature (Bio1), and ultraviolet radiation (UV-B) were the top contributors to the model output, with contribution rates of 59%, 23.6%, and 7.3%, respectively. Currently, approximately 10.15% of the total land mass is invaded by A. donax, with 21 countries, including France, Croatia, Italy, and Spain, identified as exhibiting more than 75% of their territories at high risk of invasion. However, the future projections for 2041–2060 and 2081–2100 indicated substantial expansion in suitable habitats, covering land mass proportions of 18.40% and 24.26%, respectively, under SSP2-4.5 and 19.39% and 25.66%, respectively, under SSP5-8.5. Notably, 41 countries (SSP2-4.5) and 42 countries (SSP5-8.5) were projected to shift from low to high or very high invasion risk categories from 2081–2100. Moreover, invasion risk was projected to increase across all continents, with Africa demonstrating the most significant increase (312.08%). These findings highlight the escalating threat of A. donax under global climate change and human activities, emphasizing the urgent need for proactive management strategies, including enhanced quarantine measures and effective control programs, to limit its spread and mitigate associated risks.